Characteristics of patients admitted with stroke - Mollah, AS; Rahman, SW; Das, KK; Hassanuzzaman, M (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):20-4.The abstract of this article is available on the PubMed website